Internet cambia las reglas del juego en la comunicación - Roca Ribera, Carla Lorena (2019)
The digital age has imposed its new rules of the game. The internet supposes different ways of elaborating, structuring and disseminating the news according to the language of each of the social networks. This article is an invitation to reflect on what it really implies to do digital journalism and the challenges and new functions that communicators have to face in order to survive in a digitized world, without neglecting the basic principles of journalism, that contri- bute to society.